Foetal vascular responses to thromboxane receptor blockade - B. A. Meyer; J. E. Dickinson; S. W. Walsh; V. M. Parisi (Mediators of Inflammation)
We hypothesized that foetal administration of SQ-29,548, a putative thromboxane receptor blocker, would prevent foeto–placental vasoconstriction produced by the thromboxane mimic U46619. Arterial blood gases, continuous monitoring of maternal and foetal heart rates and blood pressures were performed in chronically catheterized pregnant ewes. Foetal blood flows and vascular resistance were determined with radioactive microspheres. SQ-29,548 effectively blocked the expected vasoconstrictive effects of thromboxane. However, prolonged infusion of SQ-29,548 resulted in significant decreases in umbilical–placental blood flow and foetal mean arterial pressure. This was accompanied by a respiratory acidemia. Potential therapy for the vasoconstrictive disorders of pregnancy with SQ-29,548 awaits further investigation of its intrinsic vasoactive properties in the umbilical–placental vasculature.